2017
DOI: 10.1149/2.0561701jes
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Effects of Al Doping on the Electrochemical Properties of LiNi0.5Co0.2Mn0.3O2Using First Principles

Abstract: One of the prevailing approaches to tune properties of materials is lattice doping with metal cations. Aluminum is a common choice, and numerous studies have demonstrated the ability of Al 3+ doping to stabilize different positive electrode materials, such as Li [Ni-Co-Mn] In recent decades, rechargeable batteries have demonstrated tremendous promise as alternate energy storage devices. In particular, Li-ion batteries (LIB) have revolutionized electronic devices, ranging from portable electronics to electric v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 77 publications
8
109
0
1
Order By: Relevance
“…According to the above conclusions, research priority for solving the problems of NCM811 material should give to suppression of the oxygen evolution, followed by development of the anti-oxygen electrolytes that are chemically stable against the active oxygen evolution intermediates. In this regard, cationic doping has been proven to be particularly effective in stabilizing the lattice structure of layered transition metal oxides [48][49][50][51][52] , and nonflammable electrolytes would be a good option because of their ability in retarding the propagation of oxygen radicals [53,54] .…”
Section: Resultsmentioning
confidence: 99%
“…According to the above conclusions, research priority for solving the problems of NCM811 material should give to suppression of the oxygen evolution, followed by development of the anti-oxygen electrolytes that are chemically stable against the active oxygen evolution intermediates. In this regard, cationic doping has been proven to be particularly effective in stabilizing the lattice structure of layered transition metal oxides [48][49][50][51][52] , and nonflammable electrolytes would be a good option because of their ability in retarding the propagation of oxygen radicals [53,54] .…”
Section: Resultsmentioning
confidence: 99%
“…2 we observe that the in-Li-plane a parameter changes only slightly during delithiation, whereas the orthogonal vector, c, changes considerably, in line with previous studies on layered cathode materials. [14,21,24,39] Specifically, the a parameter decreases slightly on delithiation for LNO and LCO, while it increases for LMO. This effect may be attributed to differences in the structure of LMO (orthorhombic), and LNO and LCO (rhombohedral).…”
Section: Structural Parametersmentioning
confidence: 94%
“…Major and co‐workers elucidated the effects of Al doping on the electrochemical properties of the NCM system with the aid of theoretical predictions. [ 102 ] Considering all of the possible doping sites, the most energetically favorable structure was predicted to be stoichiometric Li[Ni 0.45 Co 0.2 Mn 0.3 Al 0.05 ]O 2 with Al substitution for Ni in each transition metal layer, as shown in Figure 14 a. The predicted formation energies of various compositions in the partially delithiated state suggested that Al‐doped NCM‐523 has a higher negative formation energy, which suggests a solid solution reaction.…”
Section: Direction Of Co‐less Ni‐rich High Capacity Cathodes For Futurementioning
confidence: 99%